European Board for Accreditation in Cardiology (EBAC) 2015 CME/CPD Survey Summary. Issue 1 (1st January 2016) - Simper, Julie; Schaefer, Robert; Griebenow, Reinhard; Michalis, Lampros; Weber, Heinz
Abstract : In the spring of 2015, the European Board for Accreditation in Cardiology (EBAC) collaborated with International CME/CPD Consulting to design and administer a survey to approximately 1, 171 professionals active in the field of European CME/CPD, with a focus on cardiology. With a nearly 5% response rate, the results herewith are non-representative, but do express current behaviours and attitudes of those active in European accredited CME/CPD.